P2.069* Factors Associated with Biologic False Positive Rapid Plasma Reagin (RPR) Serologies in HIV-1-Infected Persons. (13th July 2013) - Oboho, I; Gebo, K; Moore, R; Ghanem, K G
Abstract : Objectives: The prevalence of biologic false-positive (BFP) non-treponemal tests ranges from 4–15% among HIV-infected persons. Abnormalities in B cell function are hypothesised to increase the probability of BFP in this population. Our aim was to determine the impact of combination antiretroviral therapy (cART) and the degree of immunosuppression on BFP Rapid Plasma Reagin (RPR) tests among HIV-infected persons. Methods: We conducted a retrospective study of 711 HIV-infected patients enrolled in the Johns Hopkins HIV Clinical Cohort. BFP RPR was defined as a reactive RPR and a non-reactive FTA-ABS. We conducted two analyses: (1) A cross-sectional analysis in which patients with BFP tests were compared to two control groups: HIV-infected patients (i) with syphilis and (ii) without syphilis. (2) A longitudinal analysis to determine the factors associated with BFP persistence over time. A persistent BFP test was defined as a BFP test at all visits in patients who had more than one visit with a documented RPR test. We used logistic regression and Generalized Estimating Equations for the analyses. Results: 96 participants (13.5%) had BFP tests and 273 (48.1%) had syphilis. Twenty-two of 96 (23%) had persistent BFP tests. cART use was associated with decreased odds of BFP tests compared to persons with syphilis [adjusted odds ratio (aOR) 0.31, 95% CI: 0.15–0.63] and without syphilis [aOR 0.42 (0.22–0.81)]. cART use was also associated with decreased odds of BFP persistence over time [OR 0.07 (0.01–0.33)]. Neither CD4 count nor HIV RNA was associated with BFP test results. Lower RPR titers, injection drug use and Hepatitis B were associated with increased odds of BFP. Conclusions: The use of cART appears to significantly decrease the odds of BFP RPR tests, independent of CD4 T-cell response. This may be the result of cART's effects on B-cell functions.